Additive Manufacturing and Chemical Engineering: Looking for Synergies from a Bibliometric Study - Romero-Figueroa, J; Quijada-Maldonado, E; Abejon-Elias, R (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Additive manufacturing must be highlighted as an innovative technology with the capacity to produce objects with complex and customized geometries using a diverse range of raw materials. Despite its significant potential, research compiling and evaluating the specific contributions of additive manufacturing in the field of chemical engineering was scarce in both quantitative and qualitative terms. Similarly, the application of chemical engineering tools to additive manufacturing has not been specifically reviewed. Therefore, this work conducted a comprehensive review of the scientific literature covering these issues using bibliometric analysis. The search encompassed the entirety of the scientific literature up to the year 2023, yielding 3761 documents in the Scopus database. The principal findings of this bibliometric analysis indicated an exponential growth in the number of publications, which suggests a rising scientific interest in this field. The analysis revealed that English was the dominant language in the documents, and articles constituted the most common document type, indicating the quality and maturity of the research. The thematic distribution proved to be multidisciplinary, with a primary focus on engineering and materials science, as well as basic sciences. The United States was the foremost contributor to scientific production, followed by China and Germany. Keyword analysis and scrutiny of the most cited documents enabled the identification of the main topics, which were found to include biofabrication and biomedical applications. Moreover, bibliometric network analysis using the software SciMAT (v 1.1.06) yielded the corresponding strategic diagrams, evolution maps, and thematic networks, which provided a comprehensive overview of trends and research gaps. The considerable interest in the application of additive manufacturing to biofabrication and other biomedical purposes has overshadowed the specific applications within the chemical engineering field, while the potential contributions that chemical engineering could make to the field of additive manufacturing have been eclipsed too. On the one hand, applications focused on process intensification in chemical engineering could benefit from additive manufacturing to design advanced microreactors and other miniaturized devices or to produce more efficient heat exchangers, catalysts, and adsorbents with complex geometries and separation membranes with innovative materials and structures. On the other hand, life cycle assessment and optimization are established chemical engineering tools that should be more extensively employed in the context of additive manufacturing to ensure a more sustainable outcome. © 2025 by the authors.